Invariant manifolds for coupled nonlinear parabolic-hyperbolic partial differential equations - Fastovska, T.B. (Український математичний журнал, 2005)
We consider an abstract system of coupled nonlinear parabolic-hyperbolic partial differential equations. This system describes, e.g., thermoelastic phenomena in various physical bodies. Several results on the existence of invariant exponentially attracting manifolds for similar problems were obtained earlier. In the present paper, we prove the existence of such an invariant manifold under less restrictive conditions for a broader class of problems. Розглянуто абстрактну систему параболіко-гіперболічних пов'язаних нелінійних рівнянь з частинними похідними. Ця система описує, наприклад, термопружні явища в різних фізичних тілах. Деякі результати щодо існування інваріантних многовидів, що експоненціально притягують, для задач подібного типу було отримано раніше. В даній роботі доведено існування цього інваріантного многовиду за менш обмежувальних умов для більш широкого класу задач.